2015
DOI: 10.1182/blood-2015-01-625707
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diminution of circulating prothrombin ameliorates multiorgan pathologies in sickle cell disease mice

Abstract: • Reduced prothrombin improves survival and ameliorates inflammation and end-organ damage without spontaneous bleeding in sickle cell mice.• An individual procoagulant, prothrombin, represents a novel therapeutic target that can improve sickle cell disease outcome.Sickle cell disease (SCD) results in vascular occlusions, chronic hemolytic anemia, and cumulative organ damage. A conspicuous feature of SCD is chronic inflammation and coagulation system activation. Thrombin (factor IIa [FIIa]) is both a central pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 89 publications
3
60
1
Order By: Relevance
“…Over the ECG surveillance month, the mortality rate among the sickle mice was about 40%, consistent with the overall mortality in our Berk-SS mouse colony (56). All WT mice survived through adulthood.…”
Section: Berk-ss Mice Develop Corrected Qt Prolongation and Widening supporting
confidence: 50%
“…Over the ECG surveillance month, the mortality rate among the sickle mice was about 40%, consistent with the overall mortality in our Berk-SS mouse colony (56). All WT mice survived through adulthood.…”
Section: Berk-ss Mice Develop Corrected Qt Prolongation and Widening supporting
confidence: 50%
“…97 More recently, it has been reported that genetic deletion of circulating prothrombin alleviates multiorgan pathologies in SCD mice. 98 In addition, thrombospondin-1 can stimulate microparticle release from RBCs. These microparticles trigger reactive oxygen species production by endothelial cells, promote leukocyte adhesion, and induce endothelial apoptosis in a phosphatidylserine-dependent manner, leading to acute vaso-occlusive events in SCD mice.…”
Section: Molecules That Promote Inflammation In Scdmentioning
confidence: 99%
“…Activated platelets, in addition to sickle RBCs and leukocytes, ultimately contribute to VOC [7, 8]. Moreover, increased platelet and thrombotic activity in SCD correlates with clinical complications such as pulmonary arterial hypertension (PAH), deep vein thrombosis, and stroke [911]. Patients with SCD and mouse models show platelet activation [7, 12, 13], yet mechanisms underlying platelet dysfunction in SCD remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%